Hate Studies: The Urgency and Its Developments in the Perspective of Religious Studies - Mochamad Ziaulhaq (ARISTO, 2021)
This article is a descriptive study of hate. The phenomenon of hatred has prompted many researchers to find out more about hatred, the effects of hatred, and hate management. This research revealed that hatred had become a separate field of study, called the Hate Study, initiated and organized by the Gonzaga University Institute for Hate Studies, in 1997. Hate Studies became an international interdisciplinary field that united scholars, academic researchers, practitioners, human rights activists, policy makers, NGO leaders, and others. This study collects research results from various academic fields, both in the fields of humanities, social sciences, education, politics, economics, and the like so as to produce scientific discussions and practical applications in the academic, legal and policy settings, and counter-hate practices in community organizations civil. The purpose of this study is to illustrate the urgency of multidisciplinary religious studies disciplinary participation in hate studies, to analyze the evolution of hatred, and to find ways in dealing with the spread of hatred and violence that is needed by the plural world today. Therefore, the academic approach to religious studies will provide theoretical guidance and practice that can enrich understanding of hatred as well as dealing with the effects of hatred.